Types of planting and fertilizer organic coffee in function of the index thermal - Aparecido, Lucas Eduardo de Oliveira; Souza, Ivan Tomé de; Miranda, Gustavo Rabelo Botrel; Moraes, José Reinaldo da Silva Cabral de; Moraes-Oliveira, Adriana Ferreira de; Paula, Francisco Vitor de (Coffee Science - ISSN 1984-3909, 2017)
The implantation phase of coffee is one of the most important stages of the crop. It is worth mentioning that the different implantation systems provide different conditions for the development of crops. In addition, in order to achieve a good initial development of the coffee, the producers have applied in newly transplanted crops organic fertilizers, which has the advantage of improving soil biota, as well as reducing costs with the acquisition of mineral fertilizers. Few researches have jointly tested the efficiency of the different systems of implantation and the biological fertilization in the coffee tree. The objective of this study was to test the efficacy of different types of planting and of the biological fertilizer on the initial growth of arabica coffee, as a function of the thermal index. The experiment was developed in southern Minas Gerais, Brazil. The experimental design was in randomized blocks, in a 3 x 2 factorial scheme with 4 replicates, in a total of 6 treatments. The following were used: a) three systems of implantation (conventional planting, no-tillage in the pit and minimum cultivation); and b) two doses of the biological fertilizer (presence and absence). The growth parameters and the first coffee crop were evaluated. The evaluations were carried out according to the degree days counted from the date of planting. The results were submitted to analysis of variance. The means were grouped by the Scott-Knott method. The coffee plants implanted in the planting system “in pits” showed the best results, both in vegetative parameters and in productivity. The use of the biological fertilization in the newly transplanted arabica coffee tree did not promote improvements in the vegetative growth and first coffee production.